Construire un projet durable de prévention des TMS : dimensions stratégique et pédagogique d’une intervention ergonomique - Nadine Noyer; Flore Barcellini (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article presents a structured feed-back on an ergonomics intervention performed in a human resources headquarter of a major French region. The initial request was to help this region build a prevention "tool kit." We therefore strategically reoriented our intervention to support the development of a sustainable prevention plan. To achieve this, we designed our intervention as a teaching strategy (Dugué et al., 2010), the aim being to transform how the various actors (decision-makers, administrators, school principals...) represented the tensions between management viewpoints, work quality, and health. To do so, we combined various approaches: the construction of an explanatory model describing how musculoskeletal disorders occur on the job, an objectivation of social data at both local and regional levels, and a local activity analysis that informed these social data. These situated analyses were strategic tools used to support learning, generalization of knowledge, and changes in representations. Beside the formal dimensions of the transformations, we found that our strategy based on “adaptive” communication allowed us to garner support for our ergonomics intervention. The structured feed-back of this intervention provided an opportunity to better understand how to conduct future ergonomics intervention.